PERSPEKTIF RELATIONSHIP MARKETING DALAM PEMASARAN SYARIAH UNTUK MENINGKATKAN MINAT BELI KONSUMEN - Debby Arisandi (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
This study aims to determine the effect of relationship marketing in attracting consumers' buying intention and to find out whether the current relationship marketing is following sharia marketing. The research method used is a qualitative descriptive approach. The research was conducted in July 2020 on palm sugar craftsmen and buyers in Kaur Regency, Bengkulu Province. In this study, the sampling method used is probability sampling with a simple random sampling technique through a simple random sampling with a lottery system. The results of the study show that the relationship marketing of palm sugar craftsmen in Kaur Regency in attracting Buying Intentions is still cheating in producing palm sugar by mixing sago to harden palm sugar. This is not harmful to health but affects the quality of sugar, which is less sweet. Another result is that the relationship marketing of palm sugar craftsmen in attracting buying interest still does not match the characteristics of the sharia marketing perspective because there are still those who commit fraud in marketing sugar by reducing the sugar dose when consumer demand increases